Teacher depressive symptoms and children's school readiness in Ghana. Issue 3 (13th February 2023) - Peele, Morgan; Wolf, Sharon; Behrman, Jere R.; Aber, J. Lawrence
Abstract: This study investigated associations between kindergarten teachers' ( N = 208) depressive symptoms and students' (Ghanaian nationals, N = 1490, M age = 5.8) school‐readiness skills (early literacy, early numeracy, social–emotional skills, and executive function) across 208 schools in Ghana over one school year. Teachers' depressive symptoms in the fall negatively predicted students' overall school‐readiness skills in the spring, controlling for school‐readiness skills in the fall. These results were primarily driven by social–emotional skills ( r = .1–.3). There was evidence of heterogeneity by students' fall skill levels; teacher depressive symptoms predicted more negative spring overall school readiness for children who had higher fall school‐readiness skills. Findings underscore the importance of teachers' mental health in early childhood education globally, with implications for policy and practice.